Multiple human papillomavirus infection and high-grade cervical squamous intraepithelial lesions among women with human immunodeficiency virus: a systematic review and a meta-analysis - Cassani, Chiara; Dominoni, Mattia; Pasquali, Marianna Francesca; Gardella, Barbara; Spinillo, Arsenio (Frontiers in Medicine, 2024)
Background:To evaluate the prevalence of multiple high risk (HR) Human Papillomavirus (HPV) infection in women with Human Immunodeficiency Virus (HIV) compared to negative controls. To assess the impact of multiple HR-HPVs on the risk of high grade squamous cervical lesions (HSIL) among women with HIV.We performed a systematic search of Pubmed/Medline, Scopus, Cochrane databases and ClinicalTrials.gov from January 1, 2004 to June 30, 2023 including screenings and clinical studies evaluating the rates and role of multiple HPV infection in squamous intraepithelial lesions (SIL). Three reviewers independently screened the abstracts of the selected studies and extracted data from full-text articles. The data were subsequently tabulated and compared for consistency. The bias associated with each included study was evaluated according to the OSQE method.Results: Forty-seven studies meet definitive inclusion criteria. The quality of the observations was considered low in 26 and moderate in 21 of the included studies. In comparative screening studies, the pooled prevalence of multiple HR-HPV was 39.1% (95% CI=33.7-44.7) among women with (n=1734) and 21.6% (95%CI=17.3-26.1) in those without HIV infection (n=912) (OR=2.33,95% CI=1.83-2.97, I2=2.8%). The pooled ORs of HR-HPV multiple infection were similar in African (OR=2.72,95% CI= 1.89-3.9) and non-African countries (OR=2.1,95%CI=1.46-3, p for difference =0.96). Among women with HIV, the risk of HSIL diagnosed either by cytology or histology was higher among those with overall (OR= 2.62, 95% CI= 1.62-4.23) and high-risk multiple compared to single HPV infection (OR=1.93,95% CI= 1.51-2.46). Among women with HIV the excess rates of multiple HPV infection and the excess risk of associated HSIL were consistent across studies including both HIV-naïve subjects and those on antiretroviral therapy and in studies with different rates of immunocompromised women. When study quality (low vs moderate) was used as a moderator, the results were unchanged.Conclusions: Multiple HR-HPV infections are common among women living with HIV and are associated with an increased prevalence of HSIL. These associations were confirmed also in studies with high rates of antiretroviral therapy and low rates of immunocompromise.